Revitalization of a necrotic immature permanent anterior tooth (Case Report) - Kubba, Rabab; Al Dahan, Zainab (Journal of Baghdad College of Dentistry, 2018)
Background: Management of immature permanent teeth with necrotic pulp is considered challenging to the clinician. Regeneration of pulp tissue is a relatively new approach for management of these teeth that allow continuation of root maturation rather than formation of just a calcific barrier as in apexification. Method: 9 years-old girl with traumatized upper left central incisor. The clinical and radiographical examinations revealed uncomplicated crown fracture, tenderness to percussion, absence of response to cold vitality test. Diagnostic X-ray revealed open apex with periapical radiolucency. Revascularization was suggested to treat the tooth, starting with irrigation of canal with 5% NaOCl + 3% H2O2, followed by 2 weeks of triple antibiotic (metronidazole, ciprofloxacin and minocycline) paste application. Then antibiotic paste was removed, bleeding was induced and calcium enriched mixture (CEM) cement was applied over the blood clot and the access cavity was filled with Glass Ionomer filling material. The patient was evaluated clinically and radiographically after 1 and 7 months. Results: In clinical and radiographical examinations in follow-up visits, the tooth was asymptomatic and functional and periapical radiolucency was healed. Apical closure and positive response to cold test were noticed in the 7th month follow-up visit. Conclusion: Revascularization is an effective treatment for immature necrotic teeth. In addition, CEM cement provides favorable outcomes in revascularization treatment.